A Policy Review on Sustainability and the Three Gorges Dam in China - Langqiu Zhao (Studies in Social Science & Humanities, 2023)
The construction of large dams has become a controversial environmental issue around the world. The Three Gorges Dam on the Yangtze River in China is by far the largest hydroelectric power plant in the world. Supporters of the project argue that it would help control catastrophic flooding along the Yangtze River, provide much-needed electricity to the central region of China along the river, and enhance the economic advantage of the interior. The most important role is for the dam to act as an important power station and reservoir in the middle and lower reaches of the Yangtze River, as it will not only solve natural disasters, such as floods and mudslides, but also promote economic development in the middle and lower reaches of the Yangtze River through power generation. The dam is also intended to protect millions of people from periodic flooding along the Yangtze River, although there has been debate about its effectiveness. However, the dam has also caused damage to ecological and wildlife habitats, archaeological and cultural sites, and the displacement of millions of people.